Femoral and axillary ultrasound blood flow during exercise: A methodological study - Walter, G.; Nottin, S.; Dauzat, M.; Obert, P. (Medicine & Science in Sports & Exercise, 2006)
Purpose: To use Doppler ultrasound 1) to assess the relationship between exercise intensity and changes in femoral and axillary artery diameter, 2) to determine whether volume blood flow (BF) measured during early recovery accurately reflects exercise BF, and 3) to assess the influence of artery caliber and/or site as well as exercise intensity on BF measurement reproducibility.